Problemy komunikacji międzykulturowej w korporacjach transnarodowych - Nizielska, Aleksandra (Cross-Cultural Communication Problems in Transnational Corporations, 2008)
The paper presents specific issues resulting from intercultural communication in transnational corporate entities. Basic dimensions of national and organizational cultures are demonstrated, together with their impact on the process of intercultural communication. Models and communication styles of managers are presented, representing various cultural backgrounds, as seen in everyday work and communication activities within a transnational corporation.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 49-54